Metropolregionen als ein sich wandelndes Policy-Konzept im Vergleich - Fricke, Carola (Raumforschung und Raumordnung | Spatial Research and Planning, 2017)
In Europe, metropolitan policies emerge in a multi-scalar system of supranational, national and regional scales. Besides national policies on metropolitan issues, more and more European policies address metropolitan regions. They propose varying attributes of what characterizes a metropolitan region, for instance, defining them as functional and statistical areas, or as nodes for European spatial development. These conceptualizations of metropolitan regions have implications for institutional forms of metropolitan governance. However, existing research has not yet comparatively explored the development of metropolitan concepts in national and supranational policy contexts. This paper compares the changing concepts of metropolitan regions in the European Union, France and Germany. It raises the question of how different policies conceptualize metropolitan regions. Thereby, the paper proposes a comparative perspective on concepts in policies addressing metropolitan regions, such as policy documents, planning strategies, regulations or reports. It analyses shifts in metropolitan policies by describing the change of concepts and the reference to frames of spatial development such as polycentricity, competitiveness or integrated development. Three analytical perspectives contribute to understanding the change of metropolitan policies. First, the comparison of concepts in different national and supranational policy contexts develops an understanding of metropolitan regions beyond national specificities. Second, a historical comparison contributes to understanding changes in metropolitan concepts since the late 1990s. And third, analysing the development of metropolitan policies comparatively explores similarities of concepts and frames between policy contexts, despite differences in institutional settings.